2016
DOI: 10.2527/jas.2015-9950
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondrosis prevalence and severity at 12 and 24 weeks of age in commercial pigs with and without organic-complexed trace mineral supplementation

Abstract: Maternal and progeny diets supplemented with 2 sources of trace mineral (TM) were evaluated for effects on the size and severity of osteochondrosis (OC) lesions in progeny produced by 64 Landrace × Large White sows. At breeding, sows were randomly assigned to maternal diets (gestation and lactation) consisting 1 of 2 TM treatments. One treatment consisted of inorganic TM (ITM) with ZnO, MnSO, and CuSO at concentrations to provide 150, 50, and 16.5 mg/kg diet of Zn, Mn, and Cu, respectively. The other treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…The primary cause of lameness in growing pigs is severe OC (Ytrehus et al, 2007) with prevalence reported to be 12% and 14% (Busch and Wachmann, 2011;Grevenhof et al, 2012). Occurrence of OC is generally subclinical and starts to appear about 12 wk of age (Grevenhof et al, 2012;Tóth et al, 2016). Its progression is multifactorial (Orth, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary cause of lameness in growing pigs is severe OC (Ytrehus et al, 2007) with prevalence reported to be 12% and 14% (Busch and Wachmann, 2011;Grevenhof et al, 2012). Occurrence of OC is generally subclinical and starts to appear about 12 wk of age (Grevenhof et al, 2012;Tóth et al, 2016). Its progression is multifactorial (Orth, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is less clear whether feeding TM above requirements has potential to increase bone mineralization, strength, and joint development (Orth, 1999). A complexity of factors in OC may interact and conflicting results are often observed (Quinn et al, 2015;Tóth et al, 2016). In turkeys, additional Zn, Mn, and Cu at 40, 40, and 20 mg/kg (respectively) above NRC (1994) complexed with Met increased bone strength and health (Ferket et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondritis dissecans (OCD) is a type of osteochondrosis that affects both mammals and birds. It is considered a multifactorial disease, with hereditary and nutritional factors playing a significant role [19][20][21]. Since excessive intakes of calcium and energy are among the main factors for the development of the disease, it often affects mammals and birds kept on farms where fast growth is stimulated [22][23][24].…”
Section: Osteochondritis Dissecansmentioning
confidence: 99%
“…Importantly, these experiments did not aim to develop an animal model of human JOCD, and were performed on animal species that are ill‐suited to serve in translational studies. Both horses and domestic swine have a high incidence of naturally‐occurring OC and their size and associated housing challenges make them poor choices for long‐term studies . In our current study, we took a decidedly different route by carefully selecting a species that has a strong translational potential.…”
Section: Discussionmentioning
confidence: 99%
“…Both horses and domestic swine have a high incidence of naturally-occurring OC and their size and associated housing challenges make them poor choices for long-term studies. 37,38 In our current study, we took a decidedly different route by carefully selecting a species that has a strong translational potential. Miniature pigs are well-established as animal models of various diseases, are not known to develop naturally-occurring OC, and their vascular architecture of the epiphyseal cartilage of the distal femur is similar to that of humans'.…”
Section: Discussionmentioning
confidence: 99%